Rapid whole-genome sequencing identifies a novel GABRA1 variant associated with West syndrome - Farnaes, Lauge (Cold Spring Harb Mol Case Stud, 2017)
A 9-mo-old infant was admitted with infantile spasms that improved on administration of topiramate and steroids. He also had developmental delay, esotropia, and hypsarrhythmia on interictal electroencephalogram (EEG), and normal brain magnetic resonance imaging (MRI). West syndrome is the triad of infantile spasms, interictal hypsarrhythmia, and mental retardation. Rapid trio whole-genome sequencing (WGS) revealed a novel, likely pathogenic, de novo variant in the gene encoding γ-aminobutyric acid (GABA) type A receptor, α1 polypeptide (GABRA1 c.789G>A, p.Met263Ile) in the proband. GABRA1 mutations have been associated with early infantile epileptic encephalopathy type 19 (EIEE19). We suggest that GABRA1 p.Met263Ile is associated with a distinct West syndrome phenotype.